The Book as a Cultural Artifact in Brazilian Spiritism - André Bueno (Methexis)
Spiritism is a religious doctrine of Christian spiritualism that emerged in the 19th century in France, but which achieved great expansion and consolidation in Brazil, becoming one of the main religious expressions in the country. Brazilian Spiritism places great emphasis on the role of study as a form of knowledge and development of the doctrine, which makes the Spiritist book an important artifact in the construction of a Spiritist cultural pedagogy. In our brief text, we will see some of the particular characteristics that construct the Spiritist book as a cultural artifact, and its functions in the continuous transformation of the Brazilian Spiritist movement.